The Analysis of the Inflorescence miRNome of the Orchid Orchis italica Reveals a DEF-Like MADS-Box Gene as a New miRNA Target - Aceto, Serena (Public Library of Science, 2014)
Plant microRNAs (miRNAs) are small, regulatory non-coding RNAs involved in a wide range of biological processes, from organ development to response to stimuli. In recent years, an increasing number of studies on model plant species have highlighted the evolutionary conservation of a high number of miRNA families and the existence of taxon-specific ones. However, few studies have examined miRNAs in non-model species such as orchids, which are characterized by highly diversified floral structures and pollination strategies. Therefore, we analysed a small RNA library of inflorescence tissue of the Mediterranean orchid Orchis italica to increase the knowledge on miRNAs in a non-model plant species. The high-throughput sequencing and analysis of a small RNA library of inflorescence of O. italica revealed 23 conserved and 161 putative novel miRNA families. Among the putative miRNA targets, experimental validation demonstrated that a DEF-like MADS-box transcript is cleaved by the homolog of miR5179 of O. italica. The presence of conserved miRNA families in the inflorescence of O. italica indicates that the basic developmental flower regulatory mechanisms mediated by miRNAs are maintained through evolution. Because, according to the “orchid code” theory, DEF-like genes exert a key function in the diversification of tepals and lip, the cleavage-mediated inhibitory activity of miR5179 on a OitaDEF-like transcript suggests that, in orchids, miRNAs play an important role in the diversification of the perianth organs.